The Mediating Role of Digital Readiness in Human Capital Strategy and Employability Skills of Vocational Students - Dwi Supriono; Erny Roesminingsih; Syunu Trihantoyo; Amrozi Khamidi; Mohammad Syahidul Haq (Academic Bright Collaboration, 2026)
Purpose – This study examines the direct and indirect relationships among perceived Human Capital Strategy, Digital Readiness, and Employability Skills among vocational high school students. It also investigates whether Digital Readiness explains part of the relationship between students’ perceived educational development opportunities and employability-related competencies. Methods – A cross-sectional quantitative survey was conducted with 357 Grade XII students from six vocational high schools in Ponorogo Regency, Indonesia. Data were collected through a structured questionnaire. The proposed model was analyzed using Partial Least Squares Structural Equation Modeling in SmartPLS 4. The analysis included measurement-model assessment, structural-path estimation, explanatory power, predictive relevance, model fit, and mediation testing. Findings – Human Capital Strategy was positively associated with Employability Skills (β = 0.680, p < 0.001) and Digital Readiness (β = 0.841, p < 0.001). Digital Readiness was also positively related to Employability Skills (β = 0.208, p < 0.001). The indirect relationship through Digital Readiness was statistically significant (β = 0.175, p < 0.001). Because the direct path remained significant after the mediator was included, Digital Readiness was identified as a partial mediator. Research implications – Vocational schools should integrate digital capability development with occupational learning, workplace exposure, career preparation, and transferable-skill development. Digital readiness should therefore be strengthened as part of a broader human capital strategy rather than treated as a separate technology program. Originality – This study provides empirical evidence from Indonesian vocational education that Digital Readiness acts as a complementary pathway linking perceived human-capital-oriented educational experiences with Employability Skills.